RANCANG BANGUN APLIKASI PELAPORAN PEROKOK DI LOKASI PUBLIK BERBASIS ANDROID - Saepul Rahman (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2019)
Everything that is common in Indonesia and is not difficult to find in public places that are not areas for smoking, even though the regulations that explain the prohibition of smoking in public places already exist in the Sukabumi city regulation number 3 of 2014, and no doubt is a problem real public, which is important about the privacy of your home or other private places.It has become a habit in the community that this has been proven freely in public places. This habit is very harmful because it makes other people into passive smokers.In addition to clean air is everyone's right, but as soon as possible resulting from burning cigarettes is distributed in the air and inhaled by others, which makes other people get the same negative, and sadly some of the officers who work in local governments have been determined. Smoker reporting application in an android-based public location can be used to help and make it easier for the public to provide reports of violations of smoking in public locations to investigators or authorized officers in this case, the intended investigators are certain civil servant officials in the local government environment appointed by the authorized official in accordance with statutory provisions.